ANTROPOLOGY, MENTAL HEALTH AND UNIVERSITY CAMPUS: BEFORE AND AFTER OF COVID-19 - SUÁREZ ROJAS, Luis Alberto (2021)
This article analyses the link between mental health and the university in its relational sense, based on the narrative of university students who experience sufferings associated with mental health conditions. Considering their narratives, we will try to problematize the role played by the family and social environment and the university field, considering both the pedagogical-bureaucratic dimension and from  its relational aspect (social space, links and sense), with the purpose of reflecting on social distances, stigma and risk factors. In addition, due to the current context of the covid-19 pandemic, we have collected qualitative data that allows us to approach the experience of remote online education associated with mental health.